EUFEMISME DALAM TERAS BERITA KOMPAS TV PONTIANAK - Yesi, Kresensia; Syahrani, Agus; Muzammil, Ahmad Rabi’ul (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractEuphemism is a word in another form that is refined to avoid taboo words in a language. It can be affirmed that euphemism is an expression in the form of words or phrases that are considered to be more subtle, polite, and safe to replace other expressions. The purpose of this study is describing the use of euphemisms on the news lead of Kompas TV Pontianak. The method used in this research is descriptive method with qualitative research forms. The source of the data in this study is the news lead of Kompas TV Pontianak. The technique used in this research is documentary study technique. In this study the data collection tools used were researchers, writing instruments and supporting research instruments. The results of euphemism data analysis on the Kompas TV Pontianak news lead found five forms of euphemism including the abbreviated form (BS) of two data or 6% of the total data. Forms of eight data absorption words (BKS) or 26% of all data. Form foreign terms (BIA) one data or 3% of all data. The form of metaphor (BM) is six data or 19% of all data. Form of perifrasa (BP) fourteen data or 45% of all data. The function of euphemism is found as a tool to smooth out speech (MU) as much as twenty-seven data or 87% of all data. It functions as a diplomatic tool (AB) of four data or 13% of all data. Â Keywords: Euphemism, News Lead